2003
DOI: 10.1029/2002jb002138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low‐temperature treatments on pseudo‐Thellier paleointensity determination

Abstract: [1] In paleointensity determination on multidomain (MD) magnetite, demagnetization is always easier than restoring remanence in companion acquisition steps. As a result, paleointensity results follow a convex-down curve on the Arai plot. In an attempt to overcome this problem, the effect of systematic low-temperature demagnetization (LTD) on pseudo-Thellier results was examined. LTD was applied not only to the initial anhysteretic remanent magnetization (ARM, simulating natural remanent magnetization or NRM) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…There have been numerous studies on the lowtemperature cooling/warming cycle of natural and lab-induced remanences in zero field (referred to as low-temperature demagnetization (LTD)) for both rock and paleomagnetic applications [1][2][3][4][5][6][7][8][9][10][11][12]. One of the most striking features of LTD on magnetite is the partial demagnetization of its initial roomtemperature remanence during the LTD cycle, which results from the broadening, unpinning and reorganization of domain walls as the first magnetocrystalline anisotropy constant (K 1 ) gradually changes sign at 130 K (T k ), resulting in switching the magnetocrystalline easy axis from the body diagonal to the cube edge, or/and when magnetite experiences a phase transition from cubic to monoclinic at the Verwey transition (T v $120 K) [13].…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies on the lowtemperature cooling/warming cycle of natural and lab-induced remanences in zero field (referred to as low-temperature demagnetization (LTD)) for both rock and paleomagnetic applications [1][2][3][4][5][6][7][8][9][10][11][12]. One of the most striking features of LTD on magnetite is the partial demagnetization of its initial roomtemperature remanence during the LTD cycle, which results from the broadening, unpinning and reorganization of domain walls as the first magnetocrystalline anisotropy constant (K 1 ) gradually changes sign at 130 K (T k ), resulting in switching the magnetocrystalline easy axis from the body diagonal to the cube edge, or/and when magnetite experiences a phase transition from cubic to monoclinic at the Verwey transition (T v $120 K) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Even rocks containing SD or small PSD grains often fail to give linear Thellier results because the grains alter chemically in high‐temperature heating steps. Various correction procedures [ McClelland and Briden , 1996; Valet et al , 1996] and alternative paleointensity methods that minimize heating [ Shaw , 1974; Kono , 1978; Walton et al , 1993; Tauxe et al , 1995; Valet and Herrero‐Bervera , 2000; Pan et al , 2002; Hill et al , 2002; Yu et al , 2003] have been proposed but apart from microwave activation of magnetic spins, none really simulates the thermal aspect of the TRM/pTRM process. In the present paper, we test a low‐temperature “inverse Thellier” method that takes advantage of the fact that magnetite can be thermally demagnetized by zero‐field cooling between room temperature T 0 and the cubic‐monoclinic Verwey phase transition at T V = 120 K. Using low‐temperature demagnetization or LTD [ Heider et al , 1992] instead of conventional thermal demagnetization eliminates chemical alteration.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al (2002b) showed that, while SD and PSD grains obeyed this law, large PSD and MD grains exhibited a nonlinear behavior with the AF demagnetization of these grains generally outweighing the ARM acquisition resulting in curved pseudo-Arai plots. The use of low-temperature demagnetization (LTD) during the experiment can improve the accuracy of the field estimates, reduce the effect of MD magnetite, and consequently reduce the curvature on the pseudo-Arai plots (Yu et al, 2003b). Finally, the law of independence requires that ARM induced over mutua lly exclusive coercivity windows remain independent from one another.…”
Section: = (3)mentioning
confidence: 99%
“…The calibration of the relative pseudo-Thellier estimate for lavas has been the focus of several studies over the recent years (e.g., Yu et al, 2002b, 2003a, de Groot et al, 2013, 2014, 2015Paterson et al, 2016 and references therein). Determination of the calibratio n factors is challenging and is associated with large uncertainties (e.g., Yu et al, 2003b;Gattacceca and Rochette, 2004;Yu, 2010;de Groot et al, 2013;Lappe et al, 2013;Lerner et al, 2017). The uncertainty estimate (sB, i.e.…”
Section: = (3)mentioning
confidence: 99%